Political reforms and economic efficiency towards an economic analysis of democracy: the fundamentals of the Neo-Institutional School - Fernández-Baca, Jorge (1989)
This paper is aimed at presenting the "state of arts" of economic analysis in the study of political processes and their importance for resource allocation. The first part presents a general description of the "neoinstitutional school" as a new attempt to extend the theory of price and apply it to social and political institutions. The main developments of this school are presented in such fields as the importance of the balance of powers, the stability of political decisions in Congress and the influence of pressure groups on legislators. Finally some recommendations derived from these models are presented to improve the functioning of the Peruvian democratic system.